Old Testament Promissio and Luther's New Hermeneutic - Preus, James Samuel (Harvard theological review, 1967)
In the main stream of contemporary Luther scholarship, there is broad agreement that the emergence of “reformation theology” is organically related to, if not constituted by, a new biblical hermeneutic.Furthermore, in the search for the “sources of Luther's theology,” historians have to be, and are, frequently reminded that Luther may have gotten some of his key ideas from the Bible — however important Augustine, Bernard, Occam, Biel or Staupitz may have been for his theological formation.Accepting these two assertions, I wish to question the adequacy of the current interpretation of Luther's hermeneutical development, and to indicate the direction in which I believe the hermeneutical changes evident in Luther's earliest exegetical writing (the Dictata super psalterium, 1513–15) can help make better sense of the well-known theological innovations which appear in his writings of the 1520's.